Effectiveness of Kapsera Application on PT Trielang Jaya Maritiem - Pratama, Luthfi Dhafira (Dinasti International Journal of Digital Business Management, 2025)
This study is titled “The Effectiveness of the KAPSERA Application on Compliance and Waste Management Performance at PT Trielang Jaya Maritiem”. The background of this research arises from the issue of ship waste management that is still carried out manually, often leading to inaccuracies and low compliance with maritime regulations. The purpose of this study is to analyze the effectiveness of KAPSERA in improving waste reasonableness evaluation, enhancing crew knowledge and awareness, and its impact on compliance and waste management performance. The research employed a Research and Development (R&D) method with a mixed methods approach, involving questionnaires, interviews, observations, and system testing. Data analysis was conducted using SmartPLS to examine validity, reliability, and inter-variable relationships. The results show that the effectiveness of waste evaluation (X1) does not significantly affect compliance (Y), whereas crew knowledge and awareness (X2) have a significant positive effect on Y. These findings indicate that educational aspects are more influential in driving compliance than technical system aspects. In conclusion, KAPSERA is effective as an educational and awareness-enhancing tool, while improvements in technical evaluation features are still required to fully support operational performance